Contribution of platelet-derived microRNAs to serum microRNAs in healthy men. (3rd October 2021) - Wakabayashi, Ichiro; Sotoda, Yoko; Eguchi, Ryoji
Abstract: Platelets are a major source of microRNAs (miRNAs) in blood. Relationships between circulating platelet-derived miRNAs were investigated to elucidate their significance as biomarkers. Total miRNAs in serum were analyzed using the 3D-Gene miRNA Oligo chip. Among 22 miRNAs that are included in platelets and play functional roles, sufficient miRNA levels for comparison were detected for 11 miRNAs (let-7b-5p, miR-16–5p, miR-17–5p, miR-24–3p, miR-107, miR-126–3p, miR-150–3p, miR-191–5p, miR-197–3p, miR-223–3p, and miR-326). Among 55 pairs prepared by these miRNAs, relatively strong correlations (Spearman's correlation coefficient >0.8) were shown between miRNAs of 7 pairs including let-7b-5p and miR-16-5p, let-7b-5p and miR-17-5p, let-7b-5p and miR-107, miR-16–5p and miR-17-5p, miR-16-5p and miR-107, miR-17-5p and miR-107, and miR-107 and miR-126-3p. In principal component analysis, the first principal component consisted of let-7b-5p, miR-16-5p, miR-17-5p, miR-107, miR-126–3p, and miR-191-5p. These six miRNAs may be useful biomarkers that reflect platelet condition and function.